Increased Risk for Thromboembolism After Fontan Surgery: Considerations for Thromboprophylaxis - Van Den Helm, Suelyn; Sparks, Christopher Noel; Ignjatovic, Vera; Monagle, Paul; Attard, Chantal (Frontiers in Pediatrics, 2022)
The Fontan circulation introduces an increased risk of thromboembolism, which carry substantial mortality and morbidity. Adverse outcomes of thromboembolic complications post-Fontan surgery vary in both nature and severity, ranging from local tissue infarction and pulmonary embolism to Fontan failure and ischemic stroke. Furthermore, recent studies have identified that subclinical stroke is common yet underdiagnosed in Fontan patients. Fontan patients are commonly treated with antiplatelet agents and/or anticoagulants as primary thromboprophylaxis. Optimal thromboprophylaxis management in the Fontan population is still unclear, and clinical consensus regarding remains elusive despite the growing literature on the subject. This perspective will describe the nature of thromboembolism post-Fontan surgery, and provide evidence for the use of both current and emerging thromboprophylaxis options for children and adults living with Fontan circulation.